Diversity of retromer-mediated vesicular trafficking pathways in plants - Jha, Suryatapa Ghosh; Larson, Emily R. (Frontiers in Plant Science, 2023)
The plant endomembrane system is organized and regulated by large gene families that encode proteins responsible for the spatiotemporal delivery and retrieval of cargo throughout the cell and to and from the plasma membrane. Many of these regulatory molecules form functional complexes like the SNAREs, exocyst, and retromer, which are required for the delivery, recycling, and degradation pathways of cellular components. The functions of these complexes are well conserved in eukaryotes, but the extreme expansion of the protein subunit families in plants suggests that plant cells require more regulatory specialization when compared with other eukaryotes. The retromer is associated with retrograde sorting and trafficking of protein cargo back towards the TGN and vacuole in plants, while in animals, there is new evidence that the VPS26C ortholog is associated with recycling or ‘retrieving’ proteins back to the PM from the endosomes. The human VPS26C was shown to rescue vps26c mutant phenotypes in Arabidopsis thaliana, suggesting that the retriever function could be conserved in plants. This switch from retromer to retriever function may be associated with core complexes that include the VPS26C subunit in plants, similar to what has been suggested in other eukaryotic systems. We review what is known about retromer function in light of recent findings on functional diversity and specialization of the retromer complex in plants.